2012
DOI: 10.4172/1948-593x.1000062
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Versus Non-PEGylated γ Fe2O3@Alendronate Nanoparticles

Abstract: Thanks to their magnetic properties, superparamagnetic iron oxide nanoparticles are considered as a good delivery vehicle after grafting a therapeutical drug on their surface. For additional "stealth" characteristics, PEGylation of surfaces is necessary. The presence of PEG chains divert nanoparticles from their preferred target, the liver macrophages and increased the particle time circulation. In this work, PEG chain is added to an anticancer drug Alendronate. This molecule is grafted on iron oxide nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…11,17,19,28,36 However, the use of magnetic nanoparticles in CaP scaffolds for bone tissue engineering applications is rarely reported. In the current work, Fe 2 O 3 nanoparticles with the size of <50 nm were added to TCP precursors to achieve the Fe-doped TCP scaffolds.…”
Section: 0 Introductionmentioning
confidence: 99%
“…11,17,19,28,36 However, the use of magnetic nanoparticles in CaP scaffolds for bone tissue engineering applications is rarely reported. In the current work, Fe 2 O 3 nanoparticles with the size of <50 nm were added to TCP precursors to achieve the Fe-doped TCP scaffolds.…”
Section: 0 Introductionmentioning
confidence: 99%
“…These findings, together with no changes in vascular functions, suggested that Fe 3 O 4 @PEG-Ale do not affect negatively the endothelium and vascular smooth muscle cells of the femoral artery in rats with high BP. Similarly, Fe 3 O 4 @PEG-Ale had no negative effects in the human umbilical vein endothelial cell cultures [43].…”
Section: Discussionmentioning
confidence: 85%